Postoperative Surgical Site Infection (SSI) Rates After Elective Vs Emergency Laparotomy: An Audit - Zahra, Shamail; Waris, Hira; Khan, Bilal Irshad; Zafar, Muhammad Hassan; Shahram, Hamza; Shafiq, Muhammad Hammad (Biological and Clinical Sciences Research Journal, 2025)
Surgical site infections (SSIs) remain a significant postoperative complication following laparotomy, contributing to increased morbidity, prolonged hospital stays, and healthcare costs. Emergency laparotomies carry a higher SSI risk compared to elective procedures due to factors such as increased contamination, higher patient acuity, and complex surgical conditions. Objective: To audit and compare SSI rates in elective versus emergency laparotomy before and after implementing a structured SSI prevention bundle in a tertiary care hospital in Pakistan. Methods: This audit was conducted over two consecutive six-month periods, one before and one after implementing a WHO- and NICE-based SSI prevention bundle. Adult patients (≥18 years) undergoing elective or emergency laparotomy were included. Laparoscopic procedures, minor abdominal surgeries, and incomplete records were excluded from the analysis. The prevention bundle included timely prophylactic antibiotics, alcohol-based chlorhexidine skin preparation, intraoperative normothermia, perioperative glycaemic control, and standardized wound care. SSIs were diagnosed per CDC/NHSN definitions. Comparative analysis of pre- and post-intervention SSI rates was performed, with results expressed as percentages. Results: A total of 700 patients were included (350 per cycle), comprising 200 elective and 150 emergency laparotomies in each period. Elective SSI rates reduced from 3.5% to 2.5%, while emergency SSI rates fell more markedly from 12.0% to 7.3% after the intervention. Overall, SSI incidence declined from 7.1% pre-intervention to 4.6% post-intervention. The reduction was more pronounced in emergency cases, indicating a higher baseline risk and a greater benefit from the intervention. Conclusion: The implementation of a structured SSI prevention bundle resulted in a significant reduction in postoperative infection rates for both elective and emergency laparotomies, with the most notable improvement observed in high-risk emergency cases. These findings support the routine use of evidence-based perioperative infection prevention measures to improve surgical outcomes, particularly in resource-limited settings.